An alternative C–P cross-coupling route for the synthesis of novel V-shaped aryldiphosphonic acids - Shearan, Stephen J. I.; Andreoli, Enrico; Taddei, Marco (Beilstein Journal of Organic Chemistry, 2022)
The synthesis of phosphonate esters is a topic of interest for various fields, including the preparation of phosphonic acids to be employed as organic linkers for the construction of metal phosphonate materials. We report an alternative method that requires no solvent and involves a different order of addition of reactants to perform the transition-metal-catalyzed C–P cross-coupling reaction, often referred to as the Tavs reaction, employing NiCl2 as a pre-catalyst in the phosphonylation of aryl bromide substrates using triisopropyl phosphite. This new method was employed in the synthesis of three novel aryl diphosphonate esters which were subsequently transformed to phosphonic acids through silylation and hydrolysis.
Keywords: arylphosphonic acids; cross-coupling reaction; phosphonate esters; transition-metal catalysis

(untitled) - Demadis, K. D.; Paspalaki, M.; Theodorou, J. (Ind. Eng. Chem. Res., 2011)

(untitled) - Galezowska, J.; Gumienna-Kontecka, E. (Coord. Chem. Rev., 2012)

(untitled) - Pazianas, M.; Abrahamsen, B.; Ferrari, S.; Russell, R. G. (Ther. Clin. Risk Manage., 2013)

(untitled) - Lange, R.; ter Heine, R.; Knapp, R. (FF).; de Klerk, J. M. H.; Bloemendal, H. J.; Hendrikse, N. H. (Bone, 2016)

(untitled) - Papathanasiou, K. E.; Vassaki, M.; Spinthaki, A.; Alatzoglou, F.-E. G.; Tripodianos, E.; Turhanen, P.; Demadis, K. D. (Pure Appl. Chem., 2019)

(untitled) - Turhanen, P. A.; Demadis, K. D.; Kafarski, P. (Front. Chem. (Lausanne, Switz.), 2021)

Biogeochemistry of Chelating Agents - Nowack, B.; VanBriesen, J. M. (Chelating Agents in the Environment, 2005)

(untitled) - Wang, Y.; Stone, A. T. (Environ. Sci. Technol., 2008)

(untitled) - Bhosle, S. M.; Ponrathnam, S.; Tambe, S. S.; Chavan, N. N. (Bull. Mater. Sci., 2016)

(untitled) - Du, T.; Chen, J.; Cao, D. (J. Mater. Sci., 2001)

(untitled) - Touir, R.; Dkhireche, N.; Ebn Touhami, M.; Sfaira, M.; Senhaji, O.; Robin, J. J.; Boutevin, B.; Cherkaoui, M. (Mater. Chem. Phys., 2010)

(untitled) - Machado Fernandes, C.; Faro, L. V.; Pina, V. G. S. S.; de Souza, M. C. B. V.; Boechat, F. C. S.; de Souza, M. C.; Briganti, M.; Totti, F.; Ponzio, E. A. (Surf. Interfaces, 2020)

(untitled) - Habash, S.; Al-Banna, L. (J. Nematol., 2011)

(untitled) - Manghi, M. C.; Masiol, M.; Calzavara, R.; Graziano, P. L.; Peruzzi, E.; Pavoni, B. (Chemosphere, 2021)

(untitled) - Shimizu, G. K. H.; Taylor, J. M.; Kim, S. (Science, 2013)

(untitled) - Ramaswamy, P.; Wong, N. E.; Shimizu, G. K. H. (Chem. Soc. Rev., 2014)

(untitled) - Bao, S.-S.; Shimizu, G. K. H.; Zheng, L.-M. (Coord. Chem. Rev., 2019)

(untitled) - Bhanja, P.; Bhaumik, A. (ChemCatChem, 2016)

Metal Phosphonate Chemistry: From Synthesis to Applications - Clearfield, A.; Demadis, K. (Royal Society of Chemistry, 2011)

(untitled) - Shearan, S. J. I.; Stock, N.; Emmerling, F.; Demel, J.; Wright, P. A.; Demadis, K. D.; Vassaki, M.; Costantino, F.; Vivani, R.; Sallard, S.; Ruiz Salcedo, I.; Cabeza, A.; et al. (Crystals, 2019)

(untitled) - Sevrain, C. M.; Berchel, M.; Couthon, H.; Jaffrès, P.-A. (Beilstein J. Org. Chem., 2017)

(untitled) - Bhattacharya, A. K.; Thyagarajan, G. (Chem. Rev., 1981)

Metal Phosphonate Chemistry - Zon, J.; Garczarek, P.; BiaLek, M. (Synthesis of Phosphonic Acids and Their Esters as Possible Substrates for Reticular Chemistry, 2011)

(untitled) - Tavs, P.; Korte, F. (Tetrahedron, 1967)

(untitled) - Tavs, P.; Weitkamp, H. (Tetrahedron, 1970)

(untitled) - Heinicke, J.; Aluri, B. R.; Adam, M. S. S.; Jones, P. G. (Phosphorus, Sulfur Silicon Relat. Elem., 2008)

(untitled) - Adam, M. S. S.; Kindermann, M. K.; Köckerling, M.; Heinicke, J. W. (Eur. J. Org. Chem., 2009)

(untitled) - Beyer, O.; Homburg, T.; Albat, M.; Stock, N.; Lüning, U. (New J. Chem., 2017)

(untitled) - Hirao, T.; Masunaga, T.; Ohshiro, Y.; Agawa, T. (Tetrahedron Lett., 1980)

(untitled) - Hirao, T.; Masunaga, T.; Ohshiro, Y.; Agawa, T. (Synthesis, 1981)

(untitled) - Hirao, T.; Masunaga, T.; Yamada, N.; Ohshiro, Y.; Agawa, T. (Bull. Chem. Soc. Jpn., 1982)

(untitled) - Balthazor, T. M.; Grabiak, R. C. (J. Org. Chem., 1980)

(untitled) - Mah, R. K.; Lui, M. W.; Shimizu, G. K. H. (Inorg. Chem., 2013)

(untitled) - Hermer, N.; Stock, N. (Dalton Trans., 2015)

(untitled) - Zaręba, J. K.; Białek, M. J.; Janczak, J.; Zoń, J.; Dobosz, A. (Cryst. Growth Des., 2014)

(untitled) - Wang, Z.; Heising, J. M.; Clearfield, A. (J. Am. Chem. Soc., 2003)

(untitled) - Zheng, T.; Gao, Y.; Chen, L.; Liu, Z.; Diwu, J.; Chai, Z.; Albrecht-Schmitt, T. E.; Wang, S. (Dalton Trans., 2015)

(untitled) - Rueff, J.-M.; Perez, O.; Pautrat, A.; Barrier, N.; Hix, G. B.; Hernot, S.; Couthon-Gourvès, H.; Jaffrès, P.-A. (Inorg. Chem., 2012)

(untitled) - Rueff, J.-M.; Caignaert, V.; Chausson, S.; Leclaire, A.; Simon, C.; Perez, O.; Le Pluart, L.; Jaffrès, P.-A. (Eur. J. Inorg. Chem., 2008)

(untitled) - Taddei, M.; Costantino, F.; Vivani, R.; Sabatini, S.; Lim, S.-H.; Cohen, S. M. (Chem. Commun., 2014)

(untitled) - McKenna, C. E.; Higa, M. T.; Cheung, N. H.; McKenna, M.-C. (Tetrahedron Lett., 1977)

(untitled) - Marma, M. S.; Khawli, L. A.; Harutunian, V.; Kashemirov, B. A.; McKenna, C. E. (J. Fluorine Chem., 2005)